2021
DOI: 10.1177/00220221211044784
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and the Human Development Index Across the World

Abstract: We use annual data on over 150 countries between 2005 and 2018 to look at the relationship between subjective well-being (both cognitive and affective) and the Human Development Index (HDI). The HDI appears to be more closely related to cognitive than affective well-being. We also consider the relationships between the three HDI components (the Income, Health, and Education Indices) and well-being, and find that, on average, the Income Index has the strongest predictive power. Importantly, we find that the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…However, health expenditure reduces negative mood. Yin et al (2021) found that the health index of the Human Development Index was significantly associated with life satisfaction but unassociated with positive affect and negative affect.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, health expenditure reduces negative mood. Yin et al (2021) found that the health index of the Human Development Index was significantly associated with life satisfaction but unassociated with positive affect and negative affect.…”
Section: Discussionmentioning
confidence: 94%
“…Positive affect includes pleasant moods and emotions (i.e., joy and affection), and negative affect includes unpleasant moods and emotions (i.e., sadness, stress, worry, etc.). A few studies have assessed the association between country-level positive and negative affect and macroeconomic data (Yin et al, 2021). Therefore, the subsequent description would be about life satisfaction, happiness, or well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wellbeing of citizens is strongly correlated with the Human Development Index (HDI) and the gross national income per capita. The HDI, which consists of three core indicators: life expectancy, education level and standard of living, is higher in Spain than in Poland: Poland was ranked 32 and Spain 22 in the 2019 Human Development Report1 () (Yin, et al, 2021). The finding regarding the Spanish students' higher Openness to experience is interesting, but the literature offers little information on Openness to experience viewed from an intercultural perspective 1 http://hdr.undp.org/sites/default/files/hdr_2019_overview_-_english.pdf (McCrae, Costa, Terracciano, Parker, Mills, DeFruyt, & Mervielde, 2002;Woo, Chernyshenko, Longley, Zhang, Chiu, & Stark, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, popular societal development measures can also become culturally sensitive (Yin et al., 2021). For example, the HDI is universally calculated as a geometric mean of three sub‐indexes: economic prosperity, longevity, and education.…”
Section: Implications For Societal Development Measuresmentioning
confidence: 99%